2012
DOI: 10.1100/2012/456516
|View full text |Cite
|
Sign up to set email alerts
|

Ru (III) Catalyzed Oxidation of Aliphatic Ketones by N-Bromosuccinimide in Aqueous Acetic Acid: A Kinetic Study

Abstract: Kinetics of Ru (III) catalyzed oxidation of aliphatic ketones such as acetone, ethyl methyl ketone, diethyl ketone, iso-butylmethyl ketone by N-bromosuccinimide in the presence of Hg(II) acetate have been studied in aqueous acid medium. The order of [N-bromosuccinimide] was found to be zero both in catalyzed as well as uncatalyzed reactions. However, the order of [ketone] changed from unity to a fractional one in the presence of Ru (III). On the basis of kinetic features, the probable mechanisms are discussed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2012
2012
2015
2015

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 27 publications
0
2
0
Order By: Relevance
“…Diketones were reported as products through a rate determining reaction between protonated form of the ketone and oxidants -N-bromo saccharin [35], Nchlorosaccharin [5], Bromamine-T [36] and N-bromosuccinimide [1]. As reported by the earlier authors, the formation of diacetyl as a product of 2-butanone with these N-halogenating agents is unlikely due to the three main reasons viz., (i) In aliphatic series, it has been observed that α-diketone reacts with these halogenating agents much faster than the parent ketone.…”
Section: Mechanism and Rate Law In Absence Of Added Chloride Ionsmentioning
confidence: 99%
See 1 more Smart Citation
“…Diketones were reported as products through a rate determining reaction between protonated form of the ketone and oxidants -N-bromo saccharin [35], Nchlorosaccharin [5], Bromamine-T [36] and N-bromosuccinimide [1]. As reported by the earlier authors, the formation of diacetyl as a product of 2-butanone with these N-halogenating agents is unlikely due to the three main reasons viz., (i) In aliphatic series, it has been observed that α-diketone reacts with these halogenating agents much faster than the parent ketone.…”
Section: Mechanism and Rate Law In Absence Of Added Chloride Ionsmentioning
confidence: 99%
“…Kinetics of oxidation of ketones by different N-halo oxidants like N-bromo succinimide [1,2], 1,3-dichloro-5,5'-dimethylhydantoin [3], N-chlorosaccharin [4,5], trichloroisocyanuric acid [6,7], N-bromosaccharin [8] have received considerable attention. A thorough literature survey showed that till the date, reactions between dichloroisocyanuric acid (DCICA) and ketones were not studied.…”
Section: Introductionmentioning
confidence: 99%